The Effect of Assets Structure and Company Size on Capital Structure in Food and Beverage Companies Listed on The Indonesia Stock Exchange for The 2014-2018 Period - Rapat Piter Sony Hutauruk (Institute of Computer Science (IOCS), 2021)
This study aims to determine how the influence of asset structure and company size on food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the 2014-2018 period, totaling 14 companies. Samples were taken as many as 7 companies with a sampling technique using purposive sampling, namely where the sample was selected by adjusting to certain criteria or goals. Regression analysis method used is multiple linear regression and to test the hypothesis used t test and f test at a significant level or alpha = 5%. The research data were analyzed or processed using the SPSS version 23 program. Based on the research results, it was 0.279 or 27.9%. This shows that if the asset structure and firm size can explain the capital structure of 27.9%, the remaining 72.1% (100% - 27.9%) is explained by other variables outside this research model. In the multiple linear regression test results obtained the following regression equation: Y = 0.829 + 1.854X1 0.043X2 + e. The results of the hypothesis test state that: H1 is accepted, it can be seen from the tcount value is 3.897 > ttable 2.03452 and with a significance value of 0.000 <0.05, the asset structure affects the capital structure. H2 is rejected, it can be seen from the value of tcount is -0.686 > ttable -2.03452 and with a significance value of 0.498 > 0.05, firm size has no effect on capital structure. H3 is accepted, it can be seen from the Fcount value is 7.593 > Ftable 3.29 with a significance value of 0.002 <0.05, so the asset structure and firm size have a simultaneous effect on the capital structure.